Addivities derived from local sources for enchanced oil recovery (EOR) processes - Awang, Mariyamni; Ani, Farid Nasir; Idris, Ani; Jumari, Ira Dwiyanti; Fathaddin, Muhammad Taufiq; Goh , Meng Seng (Faculty of Chemical and Natural Resources Engineering, 2007)
The cost of chemicals prohibits many technically feasible enhanced oil recovery methods to be applied in the oilfields. This research produced surfactants from phenols that were extracted from the pyrolysis oil of oil palm shells which are a byproduct of the palm oil industry. Xanthans which are imported can be produced from many available local sources such as starches and fruits. All of the additives produced were tested for enhanced oil recovery use and were found to have suitable properties. The recoveries for surfactant polymer flooding measured in the laboratory were comparable with the values reported in literature i.e. between 7 to 15 %. This work has proved that expensive chemicals can be produced locally using local sources and byproducts, consequently posing a potential savings in EOR processes.